As we speak : how to make your point and have it stick - Meyers, Peter, 1959-; Nix, Shann (New York : Atria Books, 2012)
A practical and empowering guide to public speaking and becoming a more effective communicator in all areas of your life.
Content. Preparation ; Architecture ; Techniques -- Delivery. Voice ; Posture and movement ; Face and eyes -- State. Body ; The mind's eye ; Beliefs -- High-stakes situations. Courageous conversations ; Crisis communication ; Using technology -- Finding your voice and making it heard. Creating a personal vision ; Relationship dashboard ; Collaboration and innovation.
Includes bibliographical references (p. 273-275) and index.
Keywords: Interpersonal communication; Communication in management; Public speaking